Islamic Astronomy in Fifteenth-Century Christian Environments: Cardinal Bessarion and His Library. (3rd April 2019) - Bardi, Alberto
Abstract: This paper shows how Islamic astronomy played a significant role in the education of one of the most important Christian figures in the history of culture between eastern and western Europe, promoter of a crusade against the Ottoman Turks, namely Cardinal Bessarion (1400/1408–72). While the Byzantine polymath has generally been considered a purist of Ptolemaic astronomy, his interest in Islamic astronomy can be traced back to his youth and persisted throughout his life, as is testified by several sources from his manuscripts collection. It is misleading therefore to consider him a 'purist' of Ptolemy. The paper provides a survey of the texts of Islamic astronomy among the manuscripts of Bessarion's estate. These are compared to Ptolemaic astronomy in order to assess the importance of Islamic astronomy within the framework of Bessarion's collection. The results shed new light not only on Bessarion's astronomical interests, but also on the reception of Islamic astronomy in non-Islamicate contexts in the fifteenth century, such as the late Byzantine Empire, Rhodes, Crete, Venice, and European humanism.